2019
DOI: 10.1097/01.hs9.0000567040.38687.d3
|View full text |Cite
|
Sign up to set email alerts
|

Pb2139 Impact of Overweight in Treatment With Daratumumab in Multiple Myeloma Patients

Abstract: commencing treatment. Three patients (21.4%) relapsed with median time to relapse of 3.6 years. 15 patients (34.9%) achieved complete response after 30 days of commencing therapy and 5 patients (33.3%) relapsed with median time of 2 years. Five patients achieved very good partial response (VGPR), six patients with limited or no response. Summary/Conclusion: Renal disease is the most common presentation of AL amyloidosis followed by cardiac involvement. 2/3 of patients have elevated serum free lambda light chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A retrospective analysis reported by Rogue et al revealed no significant difference regarding overall survival and adverse events among 9 (39.1%) of 23 myeloma patients with overweight and others. 7 Our patient weighed 115 kg and had a BMI of 51 kg/ m2, which classified her as a myeloma patient with morbid obesity. Unfortunately, detailed safety data are not available for myeloma patients with overweight and obesity who are treated with daratumumab.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A retrospective analysis reported by Rogue et al revealed no significant difference regarding overall survival and adverse events among 9 (39.1%) of 23 myeloma patients with overweight and others. 7 Our patient weighed 115 kg and had a BMI of 51 kg/ m2, which classified her as a myeloma patient with morbid obesity. Unfortunately, detailed safety data are not available for myeloma patients with overweight and obesity who are treated with daratumumab.…”
Section: Discussionmentioning
confidence: 87%
“…A retrospective analysis reported by Rogue et al revealed no significant difference regarding overall survival and adverse events among 9 (39.1%) of 23 myeloma patients with overweight and others. 7…”
Section: Discussionmentioning
confidence: 99%